(3RgQI GdQjGV hfRgI GdbdhH GdeQGVs - (3SYjO Hf OGhO GdShGQj GdnqSbSjfj , CHh SdjeGf , J (B550 (3g`s ((3eMeO Hf eMeO Hf Ydj GdSgjdj s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdHQjI GdefaQO HGdCRdjI Yi eG NhdfG ef LdGFd GdfYe s
(3BNQgG (B:s
(3Efc Ydi cd TF bOjQ jG CQMe GdQGMejf hMSHfG Gddg hfYe Gdhcjd s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B- (3GdLRA (B1 - (3U (B257 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B962s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs